2020
DOI: 10.1002/oby.22752
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health in Bariatric Surgery: Selection, Access, and Outcomes

Abstract: Severe obesity has many psychiatric consequences that can be influenced by bariatric surgery. The goal of this article is to review these challenges, including the mental health status of patients with severe obesity, the evaluation of surgical candidates, and the early and late effects of the operations, and to offer some recommendations to manage these challenges. The failure of the insurance‐mandated preoperative psychosocial evaluation is also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 86 publications
1
9
0
1
Order By: Relevance
“…Indeed, 45.4% of patients were found to suffer from a psychiatric disorder. Furthermore, in accordance with previous studies [ 4 , 27 ], we found that MDD and BED were the most prevalent disorders in this population.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, 45.4% of patients were found to suffer from a psychiatric disorder. Furthermore, in accordance with previous studies [ 4 , 27 ], we found that MDD and BED were the most prevalent disorders in this population.…”
Section: Discussionsupporting
confidence: 93%
“…However, bariatric surgery was consistently associated with post-operative decreases in the prevalence of depression (seven studies; 8-74% decrease) and the severity of depressive symptoms (six studies; 40-70% decrease) (50). The increase in physical activity observed in post-bariatric surgery patients may contribute to these positive changes (46).…”
Section: The Effects Of Weight Loss On Mental Healthmentioning
confidence: 96%
“…In addition, only nine of the studies included a suitable control group. Overall, however, the larger body of evidence would suggest that, in general, weight loss is associated with improvements in psychosocial status, including health-and weight-related quality of life, self-esteem and sexual functioning (14,46). The improvements are more marked in people who undergo bariatric surgery, suggesting that the response is linked to the magnitude of weight loss (14).…”
Section: The Effects Of Weight Loss On Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Severe obesity and obesity‐related comorbid conditions have many neuropsychiatric consequences that can be influenced by bariatric surgery. Severe obesity results in increased risk of psychopathology, and the weight loss outcome of bariatric surgery results in significant reduction in psychopathology (1). Severe obesity also has negative effects on cognition (2).…”
mentioning
confidence: 99%